DIFFERENCES OF BIOACTIVE COMPOSITE RESIN COLOR ON IMMERSION IN ALCOHOL AND NON-ALCOHOL MOUTHWASH - Rosyaningsi Rosyaningsi; Isyana Erlita; Agung Satria Wardhana (Universitas Lambung Mangkurat, 2023)
Background: Composite resin is the most used material for caries restoration and highly chosen by dental patients regarding it’s high aesthetic value. People often use mouthwash to maintain dental and oral hygiene, both those containing alcohol and non-alcohol. According to several studies, the alcohol in mouthwash will cause a decrease in the physical properties of the composite resin, such as surface roughness, compressive strength, hardness, and also the aesthetic value of the composite resin. Objective: To determine the difference of bioactive composite resin color on immersion in alcohol and non alcohol mouthwash. Methods: Experimental laboratory with a pre-test and post-test with control group design using 27 samples of composite resin with a diameter of 15 mm and 1 mm. The samples were divided into 3 groups, namely the immersion group in alcoholic mouthwash, non-alcohol, and aquades. Each group consisted of 9 samples to be measured the value of color change before and after immersion for 12 hours. Results: The results of the One Way ANOVA statistical test showed that there was an effect of soaking mouthwash on the color of the bioactive composite resin. The Post Hoc LSD test showed between the alcohol and non-alcohol mouthwash group, as well as alcohol and distilled water group had a significant difference, but not in the non-alcohol mouthwash and distilled water group. Conclusion: The immersion in both alcohol and non- alcohol mouthwash are significantly affecting the color changing in bioactive composite resin. The value of color changing between mouthwash goups are significantly different. Keywords: Bioactive composite resin, discoloration, liquid absorption, mouthwash.